The Role of Customer Perceived Value in Mediating the Influence of Digital Personalization and Social Media Interaction on Repeat Purchase Intention of Consumers of Packaged Ground Coffee in Aceh - Asni, Kurnia; Chan, Syafruddin (Syiah Kuala University Press, 2025)
This study aims to analyze the influence of digital personalization and social media interaction on repeat purchase intention of packaged ground coffee in Aceh, with customer perceived value as a mediating variable. This study departs from the need to understand the effectiveness of digital marketing strategies in building consumer loyalty. Data were collected through an online survey with Google Forms distributed through WhatsApp groups using convenience and snowball sampling techniques, involving 256 respondents from various regions in Aceh such as Banda Aceh, Lhokseumawe, and Langsa. Variable measurements were adapted from previous studies and used a 5-point Likert scale. Data analysis was carried out using SPSS version 26 for reliability testing and descriptive statistics, and SmartPLS 4 for confirmatory factor analysis and structural equation modeling. The results showed that all constructs had adequate validity and reliability. Social media interaction was shown to have the greatest influence on customer perceived value, which in turn significantly increased repeat purchase intention. Digital personalization also contributed directly and indirectly to repurchase intention through perceived value. These findings provide practical implications for brand management such as Kapal Api, Nestl, and Kopi Ulee Kareng, to develop personalized, interactive, and value-based marketing strategies in the local context of Aceh. This study is also relevant for academics and marketing practitioners who are interested in understanding the integration of digitalization, social media, and consumer values in loyalty formation.